Dinâmica de CO2 e suas relações com variáveis biofísicas em área de caatinga - Melo, David Marx Antunes de (2023)
The Caatinga forest has great potential in providing ecosystem services, especially in relation to the CO2 flux balance in the soil-plant-atmosphere system. Despite this, there are still doubts about how the Caatinga will respond to the impacts of biophysical variables inherent in the CO2 balance in the face of climate change. The objective was to evaluate the impacts of biophysical variables on the CO2 flux in the soil-plant atmosphere system in a Seasonally Dry Tropical Forest. Under the hypothesis: if the biophysical variables determine the flow of CO2 in the soil-plant-atmosphere system in the caatinga, then the climatic conditions define it, because the climate regulates the processes of productivity and respiration of the ecosystem. The research was carried out at the Professor Ignácio Salcedo Experimental Station, of the Instituto Nacional do Semiárido, in the municipality of Campina Grande, Paraíba, Brazil, in a fragment of seasonally dry tropical forest under regeneration for approximately 50 years, under a lithosol Neosol. The CO2 flux was measured in a micrometeorological tower using an irga soil-flux device and Eddy Covariance measurements with daily measurements, between 2021 and 2022. The data were processed through daily analyzes of the CO2 flux averages and other variables on seasonal intervals, regression analyses, model selection and structural equation modeling. The results showed that the behavior of the CO2 flux components varied as a function of the magnitude and distribution of rainfall, showing variation with the lowest rates during the dry season and the highest rates during the wet season. Soil CO2 flux in the studied area is mainly controlled by soil moisture. Even in the dry season, gross primary productivity remained at moderate values and reached its peak in the rainy season. Ecosystem respiration was maximum in the rainy months and minimum during the dry months due to low soil moisture. Even during the dry season, the ecosystem's net CO2 exchange was in equilibrium and the Caatinga acted as an atmospheric CO2 sink during the study period. This research contributes to a better understanding of the CO2 flux variability in the soil-plant atmosphere system in seasonally dry forests of the Caatinga type, still very scarce in the literature.